Micro/nano scaffolds for osteochondral tissue engineering - Martins, Albino (2018)
To develop an osteochondral tissue regeneration strategy it is extremely important to take into account the multiscale organization of the natural extracellular matrix. The structure and gradients of organic and inorganic components present in the cartilage and bone tissues must be considered together. Another critical aspect is an efficient interface between both tissues. So far, most of the approaches were focused on the development of multilayer or stratified scaffolds which resemble the structural composition of bone and cartilage, not considering in detail a transitional interface layer. Typically, those scaffolds have been produced by the combined use of two or more processing techniques (microtechnologies and nanotechnologies) and materials (organic and inorganic). A significant number of works was focused on either cartilage or bone, but there is a growing interest in the development of the osteochondral interface and in tissue engineering models of composite constructs that can mimic the cartilage/bone tissues. The few works that give attention to the interface between cartilage and bone, as well as to the biochemical gradients observed at the osteochondral unit, are also herein described.